Artifact free reconstruction with the system matrix approach by overscanning the field-free-point trajectory in magnetic particle imaging. (18th December 2015) - Weber, A; Werner, F; Weizenecker, J; Buzug, T M; Knopp, T
Abstract: Magnetic particle imaging is a tracer-based imaging method that utilizes the non-linear magnetization response of iron-oxide for determining their spatial distribution. The method is based on a sampling scheme where a sensitive spot is moved along a trajectory that captured a predefined field-of-view (FOV). However, particles outside the FOV also contribute to the measurement signal due to their rotation and the non-sharpness of the sensitive spot. In the present work we investigate artifacts that are induced by particles not covered by the FOV and show that the artifacts can be mitigated by using a system matrix that covers not only the region of interest but also a certain area around the FOV. The findings are especially relevant when using a multi-patch acquisition scheme where the boundaries of neighboring patches have to be handled.